Digital Lending Platforms and Islamic Financial Technology in Indonesia: Reconciling Regulatory Paradigms Through Maqāṣid al-Sharīʿah and Consumer Protection Philosophies - Hutagalung, Jantarda Mauli; Suminar, M. Zaki As; Zara Pebrianto; Al-Kindi, M. Ijlal Shidqi; Masae, Murnee (JURNAL INDO-ISLAMIKA, 2025)
Indonesia’s Islamic fintech leadership necessitates aligning digital finance with Sharia governance and compliance. This study evaluates doctrinal conformity in Indonesia’s Sharia fintech ecosystem, focusing on spiritual-financial obligations (zakat, infaq, sadaqah) and commercial transactions. Through qualitative analysis of MUI fatwas, laws, and operational frameworks, systemic gaps are identified between maqāṣid al-sharīʿah (Islamic legal objectives) and current practices. Three critical deficiencies emerge: (1) ambiguous aqd (contract) standardization for P2P lending, (2) inadequate consumer data safeguards under OJK oversight, and (3) fragmented coordination between DSN-MUI and fintech operators. The research proposes a value-driven regulatory model integrating Islamic legal philosophy—prioritizing justice (‘adl), welfare (maṣlaḥah), and ethical risk-sharing—into governance structures. Such reforms could position Indonesia as a global benchmark for harmonizing faith-based economic principles with fintech innovation, ensuring legal certainty and advancing financial inclusion. By bridging jurisprudential expectations with technological advancement, this paradigm fosters sustainable Sharia compliance while strengthening inclusive digital finance ecosystems.